Analisis Kinerja Keuangan Pada Badan Pertahanan Nasional Kabupaten Tana Toraja - Novereis Novereis; Marniati Marniati; Srisetyawanie Srisetyawanie (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Analysis of Financial Performance at the National Land Agency of Tana Toraja Regency. The formulation of the problem in this study is the Financial Performance of the National Land Agency of Tana Toraja Regency. The problem in this study is how the Performance of the Revenue and Expenditure Budget at the National Land Agency of Tana Toraja Regency for the 2019-2021 Fiscal Year is viewed from the effectiveness ratio and efficiency ratio. The purpose of this study was to determine the Financial Performance of the National Land Agency of Tana Toraja Regency for the 2019-2021 Fiscal Year in terms of the effectiveness ratio and efficiency ratio. The type of research used in this research is descriptive quantitative. The type of data used in this research is quantitative data. Sources of data conducted in this study are primary data and secondary data. Data collection techniques using observation, interviews and documentation. The data analysis technique used is ratio analysis, where in the ratio analysis technique there are two formulas used to calculate the numbers, namely effectiveness and efficiency. The results showed that the Financial Performance of the National Land Agency of Tana Toraja Regency when viewed from the level of effectiveness, in 2019 with a value of 83.18% and in 2020 with a value of 90.66% and in 2021 with a value of 93.57%. efficiency in 2019 with a value of 20% in 2020 with a value of 10% and in 2021 with a value of 6%.